2023
DOI: 10.1186/s43088-023-00381-w
|View full text |Cite
|
Sign up to set email alerts
|

Combination of decaffeinated green coffee and decaffeinated green tea ameliorates cardiomyopathy through cardiotrophin-1-dependent expression regulation in a metabolic syndrome rat model: a proposed mechanism

Abstract: Background Cardiovascular diseases (CVD) are the primary medical manifestation of metabolic syndrome (MetS). Hypoxia is also involved in the pathogenesis of CVD. Since dietary intervention significantly improved the physiological condition in MetS, the development of functional food to complement conventional medical therapy is essential. Among several standard consumable products, decaffeinated green tea (DGT) and decaffeinated green coffee (DGC) have excellent activity in managing MetS-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The molecular dynamics simulation was performed using Yasara 23.4.25 (Krieger and Vriend, 2015) under AMBER14 (Maier et al, 2015). The simulation parameters were as follows: pH 5.0, 0.9% NaCl concentration, 0.997 water density, 1 atm pressure, 20 ns running time, and 310°K temperature with a cubic grid shape (Rohman et al, 2023).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…The molecular dynamics simulation was performed using Yasara 23.4.25 (Krieger and Vriend, 2015) under AMBER14 (Maier et al, 2015). The simulation parameters were as follows: pH 5.0, 0.9% NaCl concentration, 0.997 water density, 1 atm pressure, 20 ns running time, and 310°K temperature with a cubic grid shape (Rohman et al, 2023).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…11 A previous study demonstrated that GT and GC extract suppressed cardiotrophin-1 (CT-1), signal transducer and activator of transcription 3 (STAT3), GATA binding protein 4 (GATA4), and B-type natriuretic peptide (BNP) expression. 12 Therefore, GT and GC might be promising for chronic disease prevention and management. In modern pharmaceutical and natural medicine research, discovering herbal compounds and their potential therapeutic applications through computational modeling represents a promising and innovative trend.…”
Section: Introductionmentioning
confidence: 99%